2011
DOI: 10.1007/s10530-011-0111-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships of the marine invasive crab parasite Loxothylacus panopaei: an analysis of DNA sequence variation, host specificity, and distributional range

Abstract: Host specificity is a key variable of the niche breath of parasites that can be an important determinant of a parasite's ability to invade new areas. There is increasing evidence that many parasite species may comprise a variety of genetically variable lineages, which differ in host specificity and geographic range. In this study, we (1) explored the extent of diversity in the invasive parasitic barnacle Loxothylacus panopaei (Rhizocephala) infecting mud crabs (2) examined the geographic origin for the invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…However, at the South Carolina site, current infection prevalence was higher, and simulated temperature increases resulted in less dramatic prevalence declines than in Georgia; notably, the parasite persisted under the 2°C warming scenario. Our model results corroborate regional-scale observations that suggest that the parasite is thermally limited at its southern range edge (14).…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…However, at the South Carolina site, current infection prevalence was higher, and simulated temperature increases resulted in less dramatic prevalence declines than in Georgia; notably, the parasite persisted under the 2°C warming scenario. Our model results corroborate regional-scale observations that suggest that the parasite is thermally limited at its southern range edge (14).…”
Section: Methodssupporting
confidence: 86%
“…We test the prediction that parasite and host traits have different thermal performance curves and quantitatively evaluate how differences in thermal performance affect predictions of climate warming on disease dynamics. We focus on an ectothermic host-parasite system that exhibits pronounced seasonal variation in infection prevalence (13) and whose biogeographic spread might be limited by high summer temperatures (14). Eurypanopeus depressus is an abundant oyster reef-dwelling crab that is infected with a nonnative rhizocephalan parasite, Loxothylacus panopaei.…”
mentioning
confidence: 99%
“…They observed maximal variations under 1% for each of the species, and a much larger genetic differences between them, ranging from 30 to 45%. Kruse, Hare & Hines ( 2012 ) reported a more complicated genetic relationship for the rhizocephalan Loxothylacus panopaei (Gissler, 1884) on different hosts from the US East Coast. Also in this study the host association was largely responsible for genetic variations.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular tools often reveal that apparently widespread invasive species are instead cryptic species complexes, where genetic lineage may be correlated with environmental conditions (Bastrop et al 1998;FolinoRorem et al 2009;Mackie et al 2012). In an example of adaptation to a biotic agent, genetic studies strongly suggest that the parasitic castrating barnacle Loxothylacus panopaei is in fact a species complex with lineage-specific infection of its mud crab hosts (Kruse and Hare 2007;Kruse et al 2011). Comparisons of congeneric native and invasive species across several taxa have shown that the invaders often demonstrate higher tolerance of stresses than their native counterparts (Lenz et al 2011;Sorte et al 2011).…”
Section: Evidence For Genetic Adaptation In Marine Invasionmentioning
confidence: 99%
“…One shortcoming of many such studies is that it may be difficult to determine if these differences are truly heritable, or are the result of developmental or acclimatory plasticity (West-Eberhard 2003). In the case of some marine invasions, there is also the possibility that putatively population-level differences may instead be due to differences between uncharacterized cryptic species (Kruse et al 2011;Mackie et al 2012). In addition, experimental measures of differentiation may not have the resolution to detect subtle differences between populations, or may not measure the particular trait on which selection is acting.…”
Section: Introductionmentioning
confidence: 99%